Perancangan Dan Implementasi Jaringan Internet Berbasis Mikrotik - Aren Brayen Sangi; Ferdinan I. Sangkop; Olivia Kembuan (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
Sophisticated technological advances are very rare to find someone who does not use the internet network because this internet network is not only done for social media but is needed in a job. A stable internet network and wide coverage make it easier for students and teachers to access the internet for learning purposes. It is necessary to design or build a better computer network. This study uses library research methods, observation/field studies, and direct interviews to carry out data collection and develop a system used by NDLC that has been implemented and has been approved by the leadership of SMP 3 Tondano; construction has been carried out on the Internet network using the system proxy router.